Teaching self-evaluation and the quality of academic performance in students of the School of Education of the Universidad Nacional Mayor de San Marcos, 2020 - Nuñovero Gaspar , Rocio Pilar (2024)
The study to determine the relationship between teacher Self-Assessment and the Quality of Academic Performance in students of the School of Education of the Universidad Nacional Mayor de San Marcos, 2020. Teacher self-assessment had to face and adapt to changes in globalization, an essential fact for the sustainable development of university education that has experienced technological, political and socioeconomic advances, redesigning new educational schemes that seek academic excellence. That Law 30220 contemplated in the university educational system to improve. Quantitative approach, non-experimental, correlational, basic design. Applying instruments validated by experts to 15 teachers and 95 students (participants) non-probabilistic sample. Levels for teacher self-evaluation observed: medium (56.8%), high (30.5%) and low (12.6%); and in the quality of academic performance, the levels were observed: medium (45.3%), High (32.6%) and low (22.1%). In the inferential statistics, a moderate correlation was evidenced for the general hypothesis (r = 0.630); for specific 1 (r = 0.660), specific 2 (r = 0.657); and specific 3 (r = 0.704). It concluded that there is a relationship between teacher self-evaluation and the quality of academic performance in students of the Faculty of Education of the UNMSM.